Multilayer Oxygen-Scavenging Biodegradable Polylactic Acid Films Reinforced with Microcrystalline Cellulose and Butylated Hydroxytoluene: Experimental Study of Structure-Property-Function Relationships Completed with Bibliometric Analysis toward Sustainable Development Goals (SDGs) - Andi Dirpan; Mulyati M. Tahir; Serli Hatul Hidayat; Abel Yandi Novrain; Soumya Majumder; Eng Keng Seow (ASEAN Journal for Science and Engineering in Materials, 2027)
This study presents an experimental investigation of multilayer oxygen-scavenging biodegradable polylactic acid films reinforced with microcrystalline cellulose (MCC) derived from nata de coco and butylated hydroxytoluene (BHT), completed with a bibliometric analysis. Structure-property-function relationships were evaluated through morphology, mechanical performance, oxygen permeability, and biodegradability analyses. fMCC enhances matrix densification and mechanical strength while reducing oxygen permeability, although flexibility decreases. The incorporation of BHT further improves oxygen-scavenging performance. These findings support the development of advanced biodegradable packaging aligned with sustainable development goals (SDGs).